2006
DOI: 10.1556/avet.54.2006.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and features of canine atopic dermatitis in Hungary

Abstract: Medical records of 600 dogs diagnosed with atopic dermatitis were reviewed and evaluated with reference to history, geographical distribution, breed predilection, clinical signs and positive reactions to allergens as determined by intradermal skin testing (IDT) manufactured by Artuvetrin Laboratories ** . In 66.6% of dogs, the age of onset of atopic dermatitis was between 4 months and 3 years. Dogs living in the garden suburb of Budapest were more sensitive to house dust mites, fleas and moulds, and dogs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
2
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 6 publications
7
36
2
12
Order By: Relevance
“…To overcome this problem, the allergens were grouped and statistical analysis was performed on the group. As in almost all the reported surveys of CAD, house dust and house dust mites were the most common allergens in the studied populations (Saridomichelakis et al 1999;Masuda et al 2000;Mueller et al 2000;Hill and DeBoer 2001;Bensignor and Carlotti, 2002;Youn et al 2002;Zur et al 2002;Nodtvedt et al 2006;Tarpataki et al 2006;Chanthick et al 2008). This is probably a true allergic response as a good correlation between serology and IDT for the house dust mite allergens was found in a study from Japan (Masuda et al 2000).…”
Section: Allergens In Dogs With Cad and Their Associations With Signamentioning
confidence: 55%
See 2 more Smart Citations
“…To overcome this problem, the allergens were grouped and statistical analysis was performed on the group. As in almost all the reported surveys of CAD, house dust and house dust mites were the most common allergens in the studied populations (Saridomichelakis et al 1999;Masuda et al 2000;Mueller et al 2000;Hill and DeBoer 2001;Bensignor and Carlotti, 2002;Youn et al 2002;Zur et al 2002;Nodtvedt et al 2006;Tarpataki et al 2006;Chanthick et al 2008). This is probably a true allergic response as a good correlation between serology and IDT for the house dust mite allergens was found in a study from Japan (Masuda et al 2000).…”
Section: Allergens In Dogs With Cad and Their Associations With Signamentioning
confidence: 55%
“…Most of the dogs lived indoors and very few lived strictly outdoors. This was first reported in a survey of CAD in Hungary (Tarpataki et al 2006) and was recently included in the new criteria by Favrot et al (2010). Most of the dogs lived in the centre of the country, which is mostly urban.…”
Section: Signalment Of Dogs With Cadmentioning
confidence: 91%
See 1 more Smart Citation
“…Sensitisation to house dust mite and moulds account for the majority of sensitisations in dogs with atopic eczema/atopic dermatitis and illustrates the similarity of reaction patterns to environmental influences in humans and animals with respect to allergies (Zur et al, 2002). Concerning house dust mite allergens it is assumed that in dogs D. farinae plays a more important role than D. pteronyssinus (Mueller et al, 2000;Nuttall et al, 2006;Tarpataki et al, 2006), although the prevalence of the Der f1 allergen was found to be rather low in households from the UK (Raffan et al, 2005). Environmental influences including allergen and (air) pollutant exposure such as tobacco smoke may be shared by humans and their pets and contribute to the manifestation of allergies in both species.…”
Section: Discussionmentioning
confidence: 90%
“…The comparison of the results and the verification of the sensitivity and specificity of the test in case of dogs with atopic dermatitis makes it possible to assess the advantages and disadvantages of the tests and to evaluate their usefulness in the identification of the allergens and specific immunotherapy. House dust mites are the most frequently identified allergens in atopic dogs both in Europe and in the United States which is why this study concentrated exclusively on this group of allergens (Sture et al 1995, Scott et al 2001, Tarpataki et al 2006. Moreover, as year-round allergens, they are an excellent research model.…”
Section: Discussionmentioning
confidence: 94%